(untitled) (RuMoRes, 2010)
This article considers journalism as discourse, a field of production and circulation of meaning, structured by a reading contract between the enunciator and the reader. Through the perspective of French Discourse Analysis, highlights the discursive strategies of Nova, a magazine that enhances the production of meaning around an aesthetic standard that is inaccessible to most women.